2023
DOI: 10.1002/adhm.202203247
|View full text |Cite
|
Sign up to set email alerts
|

Electronic Neurons for a New Learning Paradigm

Abstract: Learning is the cornerstone of the growth and development of human beings. However, traditional learning methods are insufficient to meet the explosive growth of knowledge and information. Repeated training accounts for a large proportion of learning time, which significantly limits the improvement of learning efficiency. Inspired by cloud storage technology, electronic neurons (E‐neuron) with functions similar to neurons in the brain are proposed. Implanted E‐neurons can form new patterns of neural activity i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 37 publications
0
1
0
Order By: Relevance
“…Thus, many strategies have been explored to improve hydrogels’ mechanical properties, such as adding carbon nanotubes (CNT) and graphene. These modifications have also enhanced conductivity, making neuronal electrical stimulation possible [ 15 , 16 , 17 , 18 , 19 ]. Unfortunately, many authors have reported the toxicity of carbon derivatives, which lead to inflammation, fibrosis, lung cancer, fetal malformations, oxidative stress, and DNA damage, among others.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, many strategies have been explored to improve hydrogels’ mechanical properties, such as adding carbon nanotubes (CNT) and graphene. These modifications have also enhanced conductivity, making neuronal electrical stimulation possible [ 15 , 16 , 17 , 18 , 19 ]. Unfortunately, many authors have reported the toxicity of carbon derivatives, which lead to inflammation, fibrosis, lung cancer, fetal malformations, oxidative stress, and DNA damage, among others.…”
Section: Introductionmentioning
confidence: 99%